Longitudinal effect of sexual maturation on weight status in children aged 9 to 12 years (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2025)
Determining the stages of sexual maturation is important for observing the relationship with different factors associated with negative outcomes for the child throughout life. In this study we investigated the longitudinal effect of sexual maturation on excess body weight in children aged 9 to 12 years. This study is part of a larger study, named the Predictors of Maternal and Infant Excess Body Weight (PREDI) Study, and used data from mother-child pairs obtained at baseline and 1st, 4th and 5th follow-ups. Child sexual maturation was assessed according to Tanner stages. Descriptive analysis and Poisson regression models adjusted for important covariates were used to examine the effect of sexual maturation on the child’s weight status at 9 and 12 years of age. Being large for gestational age (42.4%) and an excessive pre-pregnancy body mass index (BMI) of the mother (42.3%) were significantly associated (p